Effect of coffee constituents, caffeine and caffeic acid on anxiety and lipopolysaccharide-induced sickness behavior in mice. (January 2020) - Mudgal, Jayesh; Basu Mallik, Sanchari; Nampoothiri, Madhavan; Kinra, Manas; Hall, Susan; Grant, Gary D.; Anoopkumar-Dukie, Shailendra; Davey, Andrew K.; Rao, C. Mallikarjuna; Arora, Devinder
Graphical abstract: Highlights: CA & CA + CAF reduce anxiety in animals and increase the exploratory behavior. LPS induces sickness behaviour in mice by producing systemic inflammation. CA & CA + CAF protects against LPS-induced behavioral and biochemical markers. Coffee constituents may have a synergistic profile in modulating neuroinflammation. Abstract: Caffeine (CAF) and polyphenolic compounds like caffeic acid (CA), chlorogenic acid and ferulic acid are commonly consumed through beverages and food. These constituents modulate immune system and impact the systemic inflammatory pathways. This study explored the modulatory effect of CA and CA + CAF on behavior and lipopolysaccharide (LPS) – induced neuroinflammation in mice. An array of behavioral tests suggest that CA (15 mg/kg) and CA + CAF (10 mg/kg + 5 mg/kg) express anxiolytic-like properties. Systemic administration of LPS (1.5 mg/kg) induced profound immobility, increased the systemic/brain cytokine (TNF-α and IL-6) levels and altered the host antioxidant defence in all the animals. Seven days pretreatment with CA alone and CA + CAF significantly reversed the LPS-induced behavioral changes and inflammatory markers. Our results suggest that the low doses of CA may offer a comparable anxiolytic and antidepressant effect when combined with CAF.